Their voices matter: student and professional perspectives on overcoming school attendance problems in the context of social, emotional, and behavioral difficulties - Enderle, Chiara; Kotschy, Louisa; Ricking, Heinrich; Kreitz-Sandberg, Susanne (Frontiers in Education, 2025)
School attendance problems (SAPs) are a growing concern worldwide, particularly among students with social, emotional, and behavioral difficulties (SEBD), who are at elevated risk of school-related stress and disengagement. While much research has focused on the factors contributing to SAPs, effectively addressing these challenges requires insights into the viewpoints of those most affected and involved in school. This qualitative study explores commonalities and differences in the perspectives of students and school-based professionals regarding prevention-focused supports and interventions for SAPs related to SEBD across levels of support. Data were collected through focus groups with school-based professionals and individual interviews with students aged 15-16 in alternative and special education settings in Saxony (Germany). Qualitative content analysis was used to identify key support strategies and elements, which were then mapped across the levels of the Multi-Dimensional Multi-Tiered System of Supports (MD-MTSS) framework. The findings reveal that trust-based relationships, coordinated school-based care, flexible learning pathways, and clear communication were central strategies identified by both groups. At the same time, differences emerged at the level of intensive interventions. Professionals emphasized legal and procedural responses, while students stressed the need for emotionally responsive environments, reduced academic pressure, and having a voice in shaping their own reintegration process. The study underscores the value of participatory, context-sensitive approaches that integrate learning and mental health support to strengthen well-being and promote school attendance, especially among students with SEBD.